The Effect of Self-Esteem on Corrupt Intention: The Mediating Role of Materialism - Liang, Yuan; Liu, Li; Tan, Xuyun; Huang, Zhenwei; Dang, Jianning; Zheng, Wenwen (Frontiers in Psychology, 2016)
The present set of studies aimed to explore the effect of self-esteem on corrupt intention and the mediating role of materialism in generating this effect. In Study 1, we used questionnaires to investigate the correlation among self-esteem, materialism and corrupt intention. In Study 2, we manipulated self-esteem to explore the causal effect of self-esteem on materialism and corrupt intention. In Study 3, we manipulated materialism to examine whether inducing materialism can reduce the relationship between self-esteem and corrupt intention. The three studies converged to show that increased self-esteem caused a low level of materialism, which in turn decreased corrupt intention. The theoretical and practical implications of the results are discussed.